Kaixin San Jiawei granule improves cognitive function and alleviates neuronal damage in Alzheimer’s disease via multi-component and multi-target mechanisms - Liu, Wei; Zhao, Yanan; Liu, Tingting; Wang, Yilei; Yin, Dongli; Zou, Shengcan; Zou, Chunze; Zhang, Zunlu; Zhi, Hongwei; Wang, Yahan (Frontiers in Pharmacology, 2025)
BackgroundKaixin San Jiawei Granule (KSG) is a traditional Chinese medicine formulation derived from classical prescriptions. Although it has shown promise in treating Alzheimer’s disease (AD), its precise mechanisms of action remain unclear. This study aimed to systematically investigate the molecular mechanisms underlying KSG’s therapeutic effects on AD through an integrative approach combining network pharmacology with experimental validation.MethodsAn in vivo AD model was established in male KM mice via intraperitoneal injection of scopolamine. Cognitive function was assessed using the Morris water maze, and hippocampal levels of acetylcholine (ACh), acetylcholinesterase (AChE), glutathione peroxidase (GSH-Px), and reactive oxygen species (ROS) were measured using ELISA. In vitro, PC12 cells were exposed to Aβ25-35 to induce apoptosis. Immunofluorescence staining, Western blotting, and qPCR were used to assess the expression of amyloid-beta (Aβ), apoptosis-related protein caspase-3, and inflammatory cytokines (TNF-α, IL-1β). Active components of KSG and their potential targets and pathways were identified using mass spectrometry and network pharmacology, while partial validation was performed using molecular docking and Western blotting.ResultsIn vivo, KSG significantly alleviated scopolamine-induced cognitive deficits in mice. Treatment increased hippocampal levels of ACh and GSH-Px while reducing AChE and ROS. In vitro, KSG mitigated Aβ25-35-induced cytotoxicity in PC12 cells, decreased Aβ accumulation, and downregulated the expression of TNF-α and IL-1β. However, KSG had no significant effect on telomerase activity, telomere length, or the expression of the telomere-associated protein POT1. Mass spectrometry and network pharmacology analyses identified genistein, quercetin, and apigenin as key active compounds with TP53, AKT1, PTGS2, and CNR2 identified as core targets. Molecular docking validation confirmed the favorable binding activity between them. The calcium signaling, PI3K-Akt, and MAPK pathways emerged as the primary enriched pathways.ConclusionKSG improves cognitive function and attenuates Aβ-induced neuronal damage in AD through multi-component, multi-target synergistic mechanisms. These effects appear to be mediated by modulation of the cholinergic system, inhibition of oxidative stress and inflammation, and suppression of neuronal apoptosis. These findings provide a theoretical basis and experimental support for developing novel AD therapies based on traditional Chinese medicine.